Die Finanzierung des öffentlich-rechtlichen Rundfunks - Karolin Herrmann (Wirtschaftsdienst, 2013)
Seit Anfang dieses Jahres wird in Deutschland der neue Rundfunkbeitrag erhoben. Im Unterschied zur vorher geltenden Rundfunkgebühr bemisst sich die Höhe der neuen Rundfunkabgabe nicht mehr nach der Zahl der vorgehaltenen Rundfunkgeräte. Sie richtet sich vielmehr an den Haushalten bzw. Betriebsstätten aus. Die entstehenden Zusatzbelastungen haben eine breite öffentliche Diskussion über die öffentlich-rechtliche Rundfunkfinanzierung entfacht. – – Germany is characterised by a dualism between public and private broadcasting. Public broadcasting services, encompassing radio and television, are mainly financed by license fees. As a result of the revised Broadcasting Law, the former broadcasting fees were replaced on 1 January 2013 by a monthly broadcasting contribution paid by every household and company regardless of whether or when they use public broadcasting services. The new system resulted in higher fees for many people and a controversial public dispute. The author of this paper highlights some options to improve the current financing system.
Keywords: H4; H5; P43; 330